2018
DOI: 10.5539/mas.v12n11p313
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Literature on the Associations among Employee Empowerment, Work Engagement and Employee Performance

Abstract: This paper is concerned with reviewing the concepts of employee empowerment, work engagement, and workforce performance. A historical overview of employee empowerment is addressed at the beginning to provide the reader with an initial understanding of the concept. Then, work engagement and employee performance concepts are reviewed deeply. Also, the links among employee empowerment, work engagement, and employee (workforce) performance are discussed through theoretical and empirical studies. This study will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 74 publications
0
25
0
1
Order By: Relevance
“…Performance should be categorised as the benchmark in acknowledging employees' contributions rather than their effectiveness. (Al-Dmour, Yassine & Masa'deh, (2018). The evaluation of employee's performance can be conducted not only for the short or long term but can also be conducted at the individual, groups or organizations level.…”
Section: Employee Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Performance should be categorised as the benchmark in acknowledging employees' contributions rather than their effectiveness. (Al-Dmour, Yassine & Masa'deh, (2018). The evaluation of employee's performance can be conducted not only for the short or long term but can also be conducted at the individual, groups or organizations level.…”
Section: Employee Performancementioning
confidence: 99%
“…Employee participation is, therefore, an endeavour of workers and their organizations, something that is positive depending on context; workers' say or voice, co-decision, industrial democracy, employee involvement, empowerment, etc. (Al-Dmour, Yassine, &Masa'deh, 2018 andMarin-Garcia &Bonavia, 2015). Employee participation implies that the employer, voluntarily or by compulsion, yields a power of decision to the employees or their representatives.…”
Section: Participation Normsmentioning
confidence: 99%
“…The five sets of workplace practices that Grawitch et al (2006) found to emerge within healthy workplaces were employee involvement, work-life balance, employee growth and development, employee recognition and health and safety. Employee involvement was defined by Grawitch and Ballard (2016, p. 5) as workplace practices that focus on "providing employees with a greater level of autonomy in their work as well as opportunities to be involved in organizational decision-making", and conceptually, employee involvement overlaps with practices such as employee empowerment, participative management and job enrichment (Al-Dmour et al, 2018). Grawitch et al (2007) found employee involvement to be the strongest predictor of organizational commitment, reduced emotional exhaustion and reduced turnover intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Administrative empowerment of employees is one of the weapons of contemporary organizations in order to face the challenges in marketplace, competition, globalization and quality in the work environment (Felemban, 2009). On the other hand, the employees satisfaction about the work environment play a critical role in improving productivity, performance and reducing employee turnover and work problems (Al-Dmour et al, 2018…”
Section: Literature Reviewmentioning
confidence: 99%